The Effect of Electronic Human Resource Management Systems on Sustainable Competitive Advantages: The Roles of Sustainable Innovation and Organizational Commitment (Global Journal of Management and Business Research, 2025)
Abstract- This study endeavors to examine the impact of electronic human resources management E-HRM systems on achieving a sustainable competitive advantage SCA in the health sector in Riyadh and Eastern region in Saudi Arabia by combine sustainable innovation SI and organization commitment OC The research was applied in health units that rely on E-HRM in their work such as electronic recruitment and online training Structured questionnaires were used to collect data from respondents Overall 575 questionnaires were distributed and received 468 response rate 81 4 The research data was analyzed using Amos- SEM Research result E-HRM have a positive and significant effect on SCA SI and OC SI and OC they have a positive and significant effect on SCA SI and OC are able to mediate the influence of E-HRM on SCA The study adds to existing literature on who E-HRM impacts SI OC and SCA
Keywords: electronic human resources management; sustainable competitive advantage